Analysis of Derivational Affixes in The Headline Articles of The Jakarta Post Newspaper (Published on January 2021) - Azhari, Rahmi; Fitrawati, Fitrawati (Universitas Negeri Padang, 2021)
This research analyzed the form and meaning of derivational affixes in the headline articles of Jakarta Post Newspaper. The form of derivational affixes is analyzed by morphological perspective and the meaning of derivational affixes is analyzed by using Leech′s (1974). The researcher used descriptive research method. The data in this research is five texts found in Jakarta Post Newspaper. The newspaper was downloaded from internet. The result of the study found that there are 70 words and 89 meaning of the derivational process that found in Jakarta Post Newspaper.